Demand side management and operational mode switching in chlorine production. Issue 7 (25th July 2018) - Brée, Luisa C.; Perrey, Karen; Bulan, Andreas; Mitsos, Alexander
Abstract : Demand side management (DSM) gains importance due to penetration of renewable energy in energy provision. A promising candidate is the chlor‐alkali process as it is an energy‐intensive process with a high installed capacity and high penetration worldwide. In this article, we consider DSM for the purpose of chlorine production via membrane electrolysis. We allow for switching between two different operational modes with different respective electrical power demands on a per ton of produced chlorine (Cl2 ) basis and different modulation of production rate. Switching necessitates a cleaning procedure leading to downtimes of the Cl2 production, while a constant provision of Cl2 for downstream processes is necessary. The optimal operation of a variable and switchable chlor‐alkali process under aforementioned constraints is determined by formulation as a mixed integer linear program. The results demonstrate that oversizing, in combination with switching, leads to substantial savings, especially in future scenarios for the electricity price. © 2018 American Institute of Chemical Engineers AIChE J, 65: e16352 2019 Abstract :